Peningkatan Kemampuan Komunikasi Matematika Dengan Strategi Problem Based Learning Pada Siswa Kelas X Semester Gasal SMK Muhammadiyah I Sukoharjo Tahun Ajaran 2015/2016 - Wibowo, Rohmad Ari, Prof. Dr. Sutama, M.Pd (2016)
The purpose of this research is to improve the communication skills of students in math class X TEI (Electronics Engineering Industry) SMK Muhammadiyah 1 Sukoharjo with problem based learning strategies. This study includes classroom action research. TEI class X with the number of 35 students to act as a receiver acts subject. Teachers of mathematics as a subject of the perpetrator, the principal and faculty as the subject of a maid. In this study the method of data collection is done by observation, tests, field notes, and documentation. Data analysis techniques began a class action until the study ended. Source data from students, teachers, and other documents related to the focus of research. The results showed an increase in mathematical communication skills to learning mathematics. The increase can be seen from the oral aspect (being able to ask, answer and conclusion) of (17.14%) to (71.43%), the written aspect (able to declare the results and using the appropriate mathematical symbol) of (22.86%) into (71.43%), the aspect of images (able to transform the problem into illustrations completion) of (20.00%) to (68.57%), explaining aspects concept (able to explain the mathematical solution) of (22.86%) into (77.14%).